The Ukrainian Pryazovye: composition, uniqueness, variability of the recreational development - Beidyk, Alexander; Komliev, Oleksandr; Donchenko, Larysa; Arsenenko, Iryna; Topalova, Olesia; Donets, Iryna (Human Geography Journal, 2022)
The regulations have been grounded in the article according to which the Ukrainian Pryazovye is positioned as the unique resource-recreational space, cultural-world outlook, landscape-physical-geographical, recreational-tourist resources (available and latent, current and potential) of which are used extremely insufficiently. Bodies, forces and phenomena of nature and society are meant by cultural and ideological resources that affect behavior, character, spiritual and physical development of man during the recreational cycle. Against the background of temporary limitation of the use by the Ukraine of the part of its Azov-Black Sea coast, the Ukrainian Pryazovye receives the option to increase its resource and recreational rating and to strengthen the national recreational and tourist branch as a whole, which requires the balanced, constructive and delicate attitude to this territory.The last consists of three sectors-connections, which are the largest by area, length and recreational mastery of which there is the Zaporizhzhya Pryazoviye. It has been emphasized that the level of ensuring of the territory of the Ukraine with recreational and tourist resources and the degree of the promotion of tourist products compared with other countries has medium and low level, the vulnerability of which during existential threats (temporary loss of the Crimea, Covid-19, the destruction of architectural and historical environment) increases at times. So, the reassessment of the eco-health-improvement and tourist meaning of the Ukrainian Pryazovye, the "reflashing" of the strategy of its further development against this background becomes more than obvious. This topicality is reinforced with the analysis of the significant array of the publications from the subject-object essence of the research, which expands and deepens the theory of resource-recreational scientific and practical direction (the number of the new concepts has been introduced), emphasizes the anthropocentric character of recreational geography, gives 5 hypothetical scenarios of the development of recreational and tourist branch in the regional and the national format on the operational perspective and contains generalizing cartographic models of the development of the regional environmental and recreational and tourist function.